Assessing the Knowledge, Adoption, and Application of Information and Communication Technologies in Select Broadcast Stations in the Federal Capital, Abuja - Jemila, Jimoh; Akase, T. M.; Akpede, K. S. (Lembaga Yasin AlSys, 2025)
This study investigates the knowledge, adoption, and application of information and communication technologies (ICTs) in selected broadcast stations within the Federal Capital Territory, Abuja. Employing a survey research design, data were collected through questionnaires administered to a cross-section of respondents. The findings indicate that ICTs have been integrated to a very high extent in the operational activities of broadcast stations. Respondents reported that the application of ICTs in Channels TV, NTA, and FRCN is particularly effective in news gathering, followed closely by satisfactory application in news processing. The study concludes that there is a high level of ICT knowledge, adoption, and application in Nigerian broadcast media, reflecting the sector’s responsiveness to technological change. It recommends continuous training of broadcast personnel in the use of modern hardware and software tools to enhance service delivery, alongside policy interventions by the National Broadcasting Commission to implement 21st-century ICT standards as advocated by the International Telecommunication Union, thereby facilitating Nigeria’s transition from analogue to digital broadcasting.